A systematic review and meta-analysis of voxel-based morphometric studies of fibromyalgia - Xin, Ming; Qu, Yuzhu; Peng, Xingfu; Zhu, Deliang; Cheng, Shirui (Frontiers in Neuroscience, 2023)
Objective Although neuroimaging investigations have revealed significant changes in brain structure in fibromyalgia (FM) patients, these findings are inconsistent. The current study conducted a systematic review and meta-analysis of voxel-based morphometric studies in order to comprehend those alterations in brain structure in FM patients. Methods Voxel-based morphometric (VBM) studies published up to January 17, 2023 were searched in the Web of Science, PubMed, EMBASE, Cochrane Library (CENTRAL), China National Knowledge Infrastructure (CNKI), Chongqing VIP, Wanfang Database. Two independent researchers carried out study screening, quality assessment, clinical data and neuroimaging data extraction. The whole-brain voxel-based gray matter (GM) data of FM patients were collected from eligible studies, and meta-analyzed using anisotropic effect size-signed differential mapping (AES-SDM). Results Twelve researches were included in this study, including 289 FM patients (mean age: 47.36 years) and 272 HS (mean age: 47.34 years). According to the meta-analysis, FM patients had increased GM in the right postcentral gyrus and left angular gyrus, and decreased GM in the right cingulate gyrus, right paracingulate gyrus, left cerebellum, and left gyrus rectus. Conclusion Our study suggests that fibromyalgia patients have altered gray matter in several brain regions that are involved in affective, cognitive functions, and in motor adaptations to pain processing.